Effect of triethylamine treatment of titanium silicalite-1 on propylene epoxidation - Xu, Juan; Wang, Yaquan; Feng, Wenping; Lin, Yi; Wang, Shuhai (Frontiers of chemical science and engineering, 2014)
Titanium silicalite-1(TS-1) treated with triethylamine (TEA) solution under different conditions was characterized by X-ray powder diffraction (XRD), Fourier-transform infrared spectrum (FTIR), ultraviolet-visible diffuse reflectance spectrum (UV-Vis), nitrogen physical adsorption and desorption, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The characterization results show that many irregular hollows are generated in the TS-1 crystals due to the random dissolution of framework silicon and the volume of the hollow cavities increase with increasing the TEA concentration, and the treatment temperature and time. The modified TS-1 samples improved in varying degrees the catalyst life for the epoxidation of propylene in a fixed-bed reactor probably due to the generation of the hollows to make it easy for the reactants and products to diffuse out of the channels.